Analysis and evaluation of the functioning of the RESPECT Index - Sikacz, Hanna; Wołczek, Przemysław (Management Sciences, 2018)
For many years, we have seen an increasing interest in corporate social responsibility (CSR). Within this concept, Socially Responsible Investing (SRI) is developing. This includes the emergence of stock indices of companies that meet the highest environmental, social and governance (ESG) requirements. Special stakeholders, such as investors, are paying more and more attention to the composition of stock exchange indices based on socially responsible companies. The presented paper discusses the topic of responsible investing in Poland, and its main aim is to analyze and evaluate the selection process of companies in the RESPECT Index and to present the evolution that has been made since its inception. However it cannot be clearly stated that the companies included in this index are characterized by a high level of implementation of CSR strategies. Stakeholders, especially investors potentially interested in investing in companies from this index, may feel some information insecurity associated with the description of the qualification of the companies in this index. They may also have some doubts as to the use of a survey to evaluate companies from ESG data
Management Sciences, 2018, vol. 23, no. 3, s. 30-38
Keywords: RESPECT index; CSR/SRI/ESG indices; responsible investing; indeks RESPECT; indeksy CSR/SRI/ESG; odpowiedzialne inwestowanie